The model of materials and structures endurance, with taking into account the evolution of their mechanical characteristics - Gorobets, V. L.; Savin, Yu. I. (Science and Transport Progress, 2008)
In the article the mathematical model describing the process of changing a limit of durability of the railway rolling stock materials and structures with taking into account the change of parameters of durability curve during loading them is presented.